Regeneration of grassland after removal of pine plantations in the north eastern mountain grasslands of the Drakensberg escarpment, Mpumalanga, South Africa - Ferguson, J. Willem H. (University of Pretoria, 2013)
Dissertation (MInstAgrar)--University of Pretoria, 2012.